2019
DOI: 10.1101/648253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrostatic interactions at the five-fold axis alter heparin-binding phenotype and drive EV-A71 virulence in mice

Abstract: 19Enterovirus A71 (EV-A71) causes hand, foot and mouth disease epidemics with neurological 20 complications and fatalities. However, the neuropathogenesis of EV-A71 remains poorly 21 understood. In mice, adaptation and virulence determinants have been mapped to mutations at 22 VP1-145, VP1-244 and VP2-149. We hypothesized that heparin-binding phenotype shapes 23 EV-A71 virulence in mice. We constructed six viruses with varying residues at VP1-98, VP1-24 145 (which are both heparin-binding determinants) and VP2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…Similar results were obtained by Fujii et al [85] using cynomolgus monkeys. More recently, Tee et al [86] generated a number of mutants that showed different degrees of heparin binding activity. They showed that weak heparin binders have a more virulent phenotype than strong heparin binders in a neonatal mouse model.…”
Section: Hsmentioning
confidence: 99%
“…Similar results were obtained by Fujii et al [85] using cynomolgus monkeys. More recently, Tee et al [86] generated a number of mutants that showed different degrees of heparin binding activity. They showed that weak heparin binders have a more virulent phenotype than strong heparin binders in a neonatal mouse model.…”
Section: Hsmentioning
confidence: 99%